The effect of annealing temperatures to prepare ZnO seeds layer on ZnO nanorods array/TiO2 nanoparticles photoanode. (February 2016) - Chou, Hsueh-Tao; Hsu, Ho-Chun
Highlights: Preparation and material properties of ZnO nanorods array/TiO2 were investigated. A novel nanostructure of ZnO nanorods array/TiO2 nanoparticles film is purposed. Long electron lifetime occurred at annealing temperature of 550 °C. Abstract: In this study, we have fabricated a ZnO nanorods array/TiO2 nanoparticles thin-film as a photoanode, and also investigated the annealing effect at various temperatures (as grown, 250 °C, 350 °C, 450 °C and 550 °C) on ZnO seeds layer. The material properties of ZnO nanorods array were investigated by field emission scanning electron microscopy (FE-SEM), energy dispersive spectrometer (EDS), X-ray diffraction (XRD) and ultraviolet visible spectroscopy. Besides, the performances of solar cells were evaluated using a source meter (Keithley 2400), which included open-circuit voltage ( V OC ), short-circuit current density ( J SC ), fill factor (F.F.) and power conversion efficiency ( η %) at one sun (A.M. 1.5G, 100 mW/cm 2 ). The electrochemical properties of the cells were analyzed by electrochemical impedance spectroscopy (EIS). From the EIS results, the cell performances were affected by annealing temperature, especially the fill-factor, at an annealing temperature of 550 °C due to the annealing treatment can enhance the connection between the interfaces of ZnO seeds/TCO, improving the electron lifetime, reducing the electron recombination loss. Finally, the sample annealing at 550 °C has the highest fill-factor of 44, power conversion efficiency of 0.19%, the highest R ct2 of 162.8 Ω and long electron lifetime of 7.25 ms.